2016
DOI: 10.2217/nnm-2016-0233
|View full text |Cite
|
Sign up to set email alerts
|

Differential Uptake of Nanoparticles by Human M1 and M2 Polarized Macrophages: Protein Corona as a Critical Determinant

Abstract: The observed differential uptake by M1 and M2 macrophages will help understand the fate of nanoparticles in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 49 publications
5
57
0
Order By: Relevance
“…Previous studies already evaluated the effect of macrophage polarization on nanoparticle uptake, but they obtained contrasting results, depending on the conditions used during the studies and, most importantly, on the type on nanoparticle used. [64][65][66] Ideally, for intravenous injectable nanosystems and the "hitchhike" effect to the infarcted heart by recruited macrophages to take place, the aim is to obtain a nanosystem that is able to associate with the macrophages' surface, without being taken-up. To understand which type of macrophage was presenting a higher nanoparticle-cell association rate versus uptake, we evaluated the interactions between the hitchhiking nanoparticles and the differentiated M1-and M2-like macrophages derived from both human and murine precursors.…”
Section: Cell-nanoparticle Interactions With Primary Macrophagesmentioning
confidence: 99%
“…Previous studies already evaluated the effect of macrophage polarization on nanoparticle uptake, but they obtained contrasting results, depending on the conditions used during the studies and, most importantly, on the type on nanoparticle used. [64][65][66] Ideally, for intravenous injectable nanosystems and the "hitchhike" effect to the infarcted heart by recruited macrophages to take place, the aim is to obtain a nanosystem that is able to associate with the macrophages' surface, without being taken-up. To understand which type of macrophage was presenting a higher nanoparticle-cell association rate versus uptake, we evaluated the interactions between the hitchhiking nanoparticles and the differentiated M1-and M2-like macrophages derived from both human and murine precursors.…”
Section: Cell-nanoparticle Interactions With Primary Macrophagesmentioning
confidence: 99%
“…Furthermore, nanoparticle internalization decreased inflammatory cytokine secretion. These trends were corroborated by Binnemars‐Postma et al, who investigated the effect of protein coronas on silica nanoparticle uptake by M1 or M2 macrophages …”
Section: Synthetic Biomaterials To Target Tams In Cancer By Systemic mentioning
confidence: 99%
“…Consequently, various anticancer therapeutics have been linked or modified with HA to increase their cellular uptake and therefore their pharmacokinetic effect on cancer cells. 122,123 For example, Figueroa et al showed how pro-apoptotic protein-HA bioconjugates can reduce at least 3-fold the cell viability of CD44 overexpressing cancer cells versus normal cells. 124 The ONCOFID™-S bioconjugate, which links the anticancer drug irinotecan and HA, showed a significant increment in drug efficacy in vitro and improved mice survival in ovarian cancer.…”
Section: Lectinsmentioning
confidence: 99%